Influence of Brain Stem on Axial and Hindlimb Spinal Locomotor Rhythm Generating Circuits of the Neonatal Mouse - Jean-Xavier, Céline; Perreault, Marie-Claude (Frontiers in Neuroscience, 2018)
The trunk plays a pivotal role in limbed locomotion. Yet, little is known about how the brain stem controls trunk activity during walking. In this study, we assessed the spatiotemporal activity patterns of axial and hindlimb motoneurons (MNs) during drug-induced fictive locomotor-like activity (LLA) in an isolated brain stem-spinal cord preparation of the neonatal mouse. We also evaluated the extent to which these activity patterns are affected by removal of brain stem. Recordings were made in the segments T7, L2, and L5 using calcium imaging from individual axial MNs in the medial motor column (MMC) and hindlimb MNs in lateral motor column (LMC). The MN activities were analyzed during both the rhythmic and the tonic components of LLA of LLA, the tonic component being used as a readout of generalized increase in excitability in spinal locomotor networks. The most salient effect of brain stem removal was an increase in locomotor rhythm frequency and a concomitant reduction in burst durations in both MMC and LMC MNs. The lack of effect on the tonic component of LLA indicated specificity of action during the rhythmic component. Cooling-induced silencing of the brain stem reproduced the increase in rhythm frequency and accompanying decrease in burst durations in L2 MMC and LMC, suggesting a dependency on brain stem neuron activity. The work supports the idea that the brain stem locomotor circuits are operational already at birth and further suggests an important role in modulating trunk activity. The brain stem may influence the axial and hindlimb spinal locomotor rhythm generating circuits by extending their range of operation. This may represent a critical step of locomotor development when learning how to walk in different conditions and environments is a major endeavor.